Propuesta de merchandising como herramienta de marketing en la decisión de compra, para incrementar las ventas de los productos en el caso "Comisariato San Andrés" en el sur de la ciudad de Quito. - Sánchez Meza, Patricia Catalina (2011)
A comprehensive proposal is developed according to the tool Merchandising providing solutions to a series of failures and in turn sought capitalize on increased sales Commissariat presents the case of "San Andrés." For its development has been considered consumer behavior at the point of sale to determine what are the elements that influence the purchase decision, and space management at the time of purchase for the products more attractive.